Ethnomedicinal Knowledge of Plants used by Local People in Buldhana District of Maharashtra (India) - Y.A. Ahirrao, D. A. Patil* and (Journal of Ecobiotechnology, 2011)
The present investigation was aimed at documentation, analysis and evaluation of ethnomedicinal knowledge in the study area as the forces of acculturation are rapid in recent times. The underprivileged tribal and rural people of Buldhana district (Maharashtra India) do not receive adequate primary healthcare.Ã‚Â They have perforce beenÃ‚Â still utilizing traditionally the plants in their surrounding for various purposes including ethnomedicine. The objective of the study was to document ethnobotanical knowledge especially of notable herbs utilized by the different backward people, whether tribal or rural, in the area under study.Ã‚Â Season-wise regular visits formed the basis of the present investigation.Ã‚Â Ethnomedicinal data was obtained through structural interviews, and discussions, following Jain (1987), with the tribal/rural informants, healers, medicine-men/women, etc. (with age between 50-65) or actual personal observations during ethnobotanical forays.Ã‚Â Minimum five to eight informants were taken into consideration for each claim.Ã‚Â This investigation brought on record that people of the study area generally utilize 62 plants species belonging 38 families.Ã‚Â Different plant parts such as fruit, stem-bark and root are most commonly employed.Ã‚Â Medicinal recipes viz. extract, powder and decoction are used in this preferential order. A fair wide range of diseases, as many as 35, are treated by people of Buldhana district using local plants. Jaundice and rheumatism are more prevalent in the study areas as compared to other diseases.Ã‚Â These ethnomedicinal claims may aid in finding novel lead molecules for welfare of mankind. The data would be useful for further scientific investigations.